Dynamic analysis of obesity formation in rats kept on a high-fat diet - I. Yu. Deulin; N. A. Palchikova; O. P. Molodykh; A. M. Sinyavskaya; A. I. Subbotovskaya; V. G. Selyatitskaya (Сибирский научный медицинский журнал, 2025)
The aim of this study was to conduct a comparative analysis of the development of obesity in rats fed a high-fat diet (HDL) for 4 and 7 weeks.   Material and methods. Sexually mature male Wistar rats were used in the work. Control animals were kept on a diet in which fat was 10–11 %, experimental rats – on an HDL, in which fat accounted for 36 % of the caloric content of the daily diet due to the addition of melted pork fat to the food. The mass of organs and adipose tissue, the content of triglycerides, total and cholesterol, high- and low-density lipoproteins, and the activity of alanine and aspartate amino transferase in blood serum were measured. Liver sections were stained with hematoxylin and eosin to assess the relative number of Kupffer cells. An indirect streptavidin peroxidase method was used for immunohistochemical examination of sections.   Results and discussion. In rats kept on HDL for 4 weeks, the following parameters increased in comparison with control animals: body weight by 21 %, mass index of retroperitoneal, epidermal and interscapular brown fat (by 56, 33 and 52 %, respectively), serum triglyceride content by 2.3 times, numerical density of Kupffer cells by 2.1 times, the expression of matrix metalloproteinase 9 in the liver by 2.8 times. After 7 weeks of HDL, alanine amino transferase activity in serum increased by 20 %, the numerical density of Kupffer cells remained 2.1-fold increased, and the expression level of matrix metalloproteinase 9 raised 5-fold relative to control rats.   Conclusions. After 4 weeks of HDL treatment, the rats developed an obesity phenotype, accompanied by negative shifts in the structural and functional state of the liver; after 7 weeks, these negative changes worsened, which allows us to consider the used model of obesity in rats as a tool for studying the effectiveness of approaches to normalizing obesity and related diseases.